Evaluating the Effectiveness of School-Based Support Programmes for Pregnant Teenagers: A Case Study of Bohlabela District, Mpumalanga - Mhlanga, Patricia Boipilo; Ikhile, Ikekhwa Albert (Journal of Ecohumanism, 2025)
Background Adolescent pregnancy remains a persistent challenge in South Africa, particularly in rural areas where socio-economic and cultural barriers compound the educational vulnerabilities of teenage mothers. Despite national policies advocating for the retention and support of pregnant learners, implementation remains inconsistent. This study evaluates the effectiveness of school-based support programmes for pregnant teenagers in the Bohlabela District, Mpumalanga.Methods A qualitative case study approach was employed, involving in-depth interviews with 20 pregnant learners and focus group discussions with 6 educators from two high schools. Data were analysed thematically using Braun and Clarke’s framework to explore learners’ experiences and institutional responses to their educational needs.Results Findings revealed five major themes: informal and inconsistent programme delivery; academic disengagement because of absenteeism and fatigue; absence of psychosocial support services; pervasive stigma and discrimination; and systemic barriers such as the lack of intersectoral collaboration. While some educators offered ad hoc emotional or academic support, the lack of structured institutional mechanisms hindered continuity of learning and well-being.Conclusion The study highlights a critical gap between policy rhetoric and practical implementation. School-based support for pregnant learners remains fragmented, with negative implications for educational outcomes and emotional health. Effective reintegration requires formalised, multisectoral interventions, stigma reduction strategies, and mental health services within school systems. Strengthening institutional capacity and interdepartmental collaboration is essential to promote equitable educational access for adolescent mothers in rural settings.